Kindred Souls: A Screenplay on the Effects of Domestic Abuse on Teenagers - Miriam Christiane (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
The topic of my work is about domestic abuse on teenagers and the theme is the effects of abuse on the teenagers. This is a screenplay contains the two stories of two high school students who got the same experience which is being abuse by their family in their daily life. The purpose of making this project is that I want people to question themselves and to be aware of what they are doing to their own children or family member. Unintentional or well-intentional the action, abusive behavior should be stopped. To shape the conflicts and characterization of my characters I use three theories; parental control, frustration-aggression, and effects of abuse. As for the genre, I choose tragedy for it will help me create the ending. In the end, both students want to seek freedom by running away. However, what will happen later is not as planned.